Thyroid function in pregnancy - Muller, Ilaria; Taylor, Peter N.; Lazarus, John H. (Annals of Thyroid; Vol 3 (November 2018): Annals of Thyroid, 2018)
Thyroid hormones are essential for pregnancy maintenance and correct foetal development; even a mild thyroid disturbance can cause potential adverse consequences on obstetric outcomes and foetal well-being. Pregnancy also places substantial demands on the thyroid axis, with consequent increase of thyroid hormone requirements. Thus, it is critical to maintain appropriate levels of iodine and thyroid hormones during pregnancy. Thyroid disorders are relatively common in pregnancy, and a prompt diagnosis of thyroid dysfunction requiring medical intervention is needed. Data from large population cohorts and randomised clinical trials demonstrated that it is challenging to establish precise cut-offs of thyroid dysfunction in pregnancy, and therefore diagnose milder forms of thyroid dysfunction. There is now a growing awareness of the need for greater clarity with regard to gestational thyroid reference ranges which should not only be trimester specific, but also population and laboratory method specific. Sub-optimal thyroid function might also be exacerbated by the presence of thyroid autoantibodies, especially anti-thyroid peroxidase antibodies; such evidence led to a change in the most recent American Thyroid Association guidelines. Overt thyroid dysfunction is associated with adverse outcomes, particularly foetal loss, and early gestational age at delivery; there is universal agreement about the absolute necessity to treat such conditions. On the other hand it is unclear whether marginal thyroid abnormalities, such as subclinical hypothyroidism (ScHypo) and isolated hypothyroxinemia (IH), have sufficient impact to justify widespread screening for thyroid disease in pregnancy. This has led to substantial discrepancies between societal guidelines. More recently concern has also been raised regarding over-treatment of hypothyroidism which may result in adverse neurocognitive outcomes. There is a pressing need for evidence-based studies to determine whether universal thyroid screening in pregnancy is appropriate. Iodine deficiency and endocrine disruptors are also likely to have similar deleterious impacts as thyroid insufficiency and greater clarity is also needed here.